(untitled) (Libellarium: journal for research in the field of information and related sciences, 2013)
The aim of the paper is to present of the possibilities of positioning and visual markup of historical cadastral maps onto Google maps using open source software. The corpus is stored in the Croatian State Archives in Zagreb, in the Maps Archive for Croatia and Slavonia. It is part of cadastral documentation that consists of cadastral material from the period of first cadastral survey conducted in the Kingdom of Croatia and Slavonia from 1847 to 1877, and which is used extensively according to the data provided by the customer service of the Croatian State Archives. User needs on the one side and the possibilities of innovative implementation of ICT on the other have motivated the development of the system which would use digital copies of original cadastral maps and connect them with systems like Google maps, and thus both protect the original materials and open up new avenues of research related to the use of originals. With this aim in mind, two cadastral map presentation models have been created. Firstly, there is a detailed display of the original, which enables its viewing using dynamic zooming. Secondly, the interactive display is facilitated through blending the cadastral maps with Google maps, which resulted in establishing links between the coordinates of the digital and original plans through transformation. The transparency of the original can be changed, and the user can intensify the visibility of the underlying layer (Google map) or the top layer (cadastral map), which enables direct insight into parcel dynamics over a longer time-span. The system also allows for the mark-up of cadastral maps, which can lead to the development of the cumulative index of all terms found on cadastral maps. The paper is an example of the implementation of ICT for providing new services, strengthening cooperation with the interested public and related institutions, familiarizing the public with the archival material, and offering new possibilities for the pedagogical activities of the archives.